Free breathing three‐dimensional late gadolinium enhancement cardiovascular magnetic resonance using outer volume suppressed projection navigators. Issue 4 (28th April 2016) - Menon, Rajiv G.; Miller, G. Wilson; Jeudy, Jean; Rajagopalan, Sanjay; Shin, Taehoon
Abstract : Purpose: To develop a three‐dimensional, free‐breathing, late gadolinium enhancement (3D FB‐LGE) cardiovascular magnetic resonance (CMR) technique, and to compare it with clinically used two‐dimensional breath‐hold LGE (2D BH‐LGE). Methods: The proposed 3D FB‐LGE method consisted of inversion preparation, inversion delay, fat saturation, outer volume suppression, one‐dimensional projection navigators, and a segmented stack of spirals acquisition. The 3D FB‐LGE and 2D BH‐LGE scans were performed on 29 cardiac patients. Qualitative analysis and quantitative analysis (in patients with scar) were performed. Results: No significant differences were noted between the 3D FB‐LGE and 2D BH‐LGE data sets in terms of overall image quality score (2D: 4.69 ± 0.60 versus 3D: 4.55 ± 0.51, P = 0.46) and image artifact score (2D: 1.10 ± 0.31 versus 3D: 1.17 ± 0.38; P = 0.63). The average difference in fractional scar volume between the 3D and 2D methods was 1.9% (n = 5). Acquisition time was significantly shorter for the 3D FB‐LGE over 2D BH‐LGE by a factor of 2.83 ± 0.77 ( P < 0.0001). Conclusions: The 3D FB‐LGE is a viable option for patients, particularly in acute settings or in patients who are unable to comply with breath‐hold instructions. Magn Reson Med 77:1533–1543, 2017. © 2016 International Society for Magnetic Resonance in Medicine